Pendampingan dan Edukasi tentang Komunikasi Efektif untuk Pelestarian Lingkungan dan Pemilahan Sampah kepada Anak: Penyuluhan tentang Komunikasi Efektif untuk Pelestarian bagi Warga sekitar RPTRA Flamboyan, Tebet, Jakarta Selatan - Soemardjo, Herta A.; Liana, Chendi; Siswanto, Abdul Harif (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Household waste pollution remains a common problem. Various efforts have been made by government and non-governmental institutions to contribute to tackling household waste. Not only waste banks, but now many institutions offer services to accommodate recyclable or reusable waste. Environmental care campaigns are one effort to convey information or ideas about the importance of protecting and preserving the environment we live in, namely the earth. The mentoring method was carried out by providing and explaining materials, questions and answers (discussions) as well as providing examples regarding environmental sustainability education and waste management which was conducted on August 21, 2023 located at the Flamboyan RPTRA, Menteng Dalam Village, Tebet District, South Jakarta. The activity was held by the PKM team from Sahid University with 14 RPTRA residents and 2 people from the local village. The PKM team consisted of 3 lecturers and 5 students providing campaign materials and examples. The results of this activity are that online materials have been provided on effective communication for environmental campaigns and waste management by the Communication lecturers team from Sahid University. Furthermore, examples of how to convey campaigns were submitted by PKM students. At the end of the event the PKM team also asked participants about their impressions after participating in the mentoring. Good impressions were obtained that participants became more aware of effective ways to communicate with children regarding environmental conservation and waste sorting.